2021
DOI: 10.1016/j.isci.2021.102837
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle-disease-virus-induced ferroptosis through nutrient deprivation and ferritinophagy in tumor cells

Abstract: Highlights Oncolytic viruses NDV caused tumor cells death through ferroptosis NDV-induced ferroptosis acts through nutrient deprivation by suppression of System Xc À P53 activation is required for NDV-induced ferroptosis initiation Ferritinophagy induced by NDV promotes ferroptosis through release of ferrous iron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…Previous studies have shown that SARS-CoV-2 can induce these three kinds of programed cell death in susceptible epithelial cells and immune cells [23][24][25]. As for ferroptosis, whose morphological and biochemical features are distinct from PANoptosis, new castle virus (NDV) was the first virus to be discovered as a ferroptosis inducer in tumor cells [26]. NDV infection reduced the expression of Slc7a11 and Gpx4, resulting in the ferroptosis of infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SARS-CoV-2 can induce these three kinds of programed cell death in susceptible epithelial cells and immune cells [23][24][25]. As for ferroptosis, whose morphological and biochemical features are distinct from PANoptosis, new castle virus (NDV) was the first virus to be discovered as a ferroptosis inducer in tumor cells [26]. NDV infection reduced the expression of Slc7a11 and Gpx4, resulting in the ferroptosis of infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we showed for the first time that an oncolytic VV did not induce ferroptosis in cancer cells. However, another type of OV, Newcastle-disease virus, can induce ferroptosis in infected tumor cells [ 48 ]. It is interesting to note that ferroptosis and apoptosis can interact through certain signaling pathways, and inducers for apoptosis and ferroptosis may lead to improved tumoricidal efficacy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological hallmarks of NDV-induced apoptosis, as visualized by confocal microscopy images of infected HeLa cells, were: (i) active apoptosis with cellular shrinkage and DNA fragmentation, (ii) advanced apoptosis displaying extensive membrane blebbing, and (iii) late apoptosis showing apoptotic bodies [54]. NDV induces multimodal cell death responses according to programmed cell death, including apoptosis [37], autophagic cell death [44], necroptosis [37], pyroptosis [55], and ferroptosis [56].…”
Section: Tumor-selective Oncolysis: Intrinsic Signaling Pathwaysmentioning
confidence: 99%
“…Another way to break resistance to apoptosis is to use a different way of programmed cell death. Ferroptosis is a new form of programmed cell death that is induced by NDV [56]. It involves the activation of p53 [79], downregulation of extracellular cystine uptake by xCantiporter [80], and iron-dependent accumulation of reactive oxygen species (ROS), leading to lethal levels of phospholipid peroxides.…”
Section: Breaking Cancer Therapy Resistanciesmentioning
confidence: 99%
See 1 more Smart Citation